Three-dimensional localization of gas leakage using acoustic holography. (15th May 2022) - Li, Lei; Wang, Shenghui; Li, Feng; Zheng, Xiya; Wu, Yongqing; Gao, Yang; Qiao, Yingying
Highlights: A novel visualized 3D localization approach for gas leakage. Sound field reconstruction using far-field acoustic holography theory. Depth information of the leakage source can be obtained to realize 3D localization. Virtual array is introduced to reduce system complexity and improve feasibility. Abstract: Gas leakage localization is essential to prevent accidents from gas transportation or storage failures. There have been extensive studies on one-dimensional (1D) and two-dimensional (2D) gas leakage localization problem. This paper is the first to report the demonstration of a three-dimensional (3D) localization of gas leaks using far-field acoustic holography. This approach simultaneously provides 2D sound field imaging and depth position information regarding the leakage source. A virtual phased array composed of only two sensors collects the needed data, resulting in improved accuracy, enhanced feasibility and reduced cost. Various parameters, including the number of sensors, the spacing of array elements and the distance to the leakage source, are analyzed by a simulation of leakage sound field reconstruction. A series of experiments validated the effectiveness and accuracy of the proposed approach. Our results demonstrate that the proposed method achieves 3D localization and high-resolution imaging recognition of gas leaks.